2000
DOI: 10.1034/j.1600-0420.2000.078004425.x
|View full text |Cite
|
Sign up to set email alerts
|

Mohs' micrographic surgery for basal cell carcinomas on the eyelids and medial canthal areaI

Abstract: ABSTRACT.Purpose: To analyse the characteristics of eyelid basal cell carcinomas excised using Mohs' micrographic technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 15 publications
0
2
1
1
Order By: Relevance
“…Other authors have also observed the high prevalence of nodular BCC on the eyelids, which has been predominant type in this location. 10,11 In contrast, the superficial type of BCC appeared to be more typical for trunk and extremities, developing seldom on face; there were no superficial BCCs located on the eyelids in our patients. These differences in distribution of various types of BCC have been already observed.…”
Section: Discussioncontrasting
confidence: 64%
“…Other authors have also observed the high prevalence of nodular BCC on the eyelids, which has been predominant type in this location. 10,11 In contrast, the superficial type of BCC appeared to be more typical for trunk and extremities, developing seldom on face; there were no superficial BCCs located on the eyelids in our patients. These differences in distribution of various types of BCC have been already observed.…”
Section: Discussioncontrasting
confidence: 64%
“…Other evidence for MMS efficacy comes largely from observational studies (Table 1 provides a summary of recurrence data). Only a few were multicentre [9][10][11][12][13][14][15] (many of which sampled the same Australian MMS database) with a follow-up of > 5 years, 9,[11][12][13][14][16][17][18][19][20][21][22] but there was significant loss to follow-up over time. Recurrence rates varied considerably.…”
Section: Recurrence/complete Excisionmentioning
confidence: 99%
“…Hence, our material has a different case mix from many other publications on the results of surgery according to Mohs. Our group has previously presented a study using a smaller base of material with shorter follow-up times ( 19 , 20 ).…”
mentioning
confidence: 99%